2008
DOI: 10.1158/1055-9965.epi-07-2697
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Markers for Monitoring Response to Therapy: Evidence for Higher Bone Specificity by a Novel Marker Compared with Routine Markers

Abstract: The aim of the present study was to compare a novel marker for high bone turnover with two routine markers for screening in prostate cancer patients. The markers were evaluated in two studies: (a) a crosssectional study of 170 prostate cancer patients with local disease stratified by Flymph node metastases (N 0 , N 1 ) compared with controls and (b) a longitudinal study of 40 hormone refractory prostate cancer patients stratified by skeletal involvement and followed during docetaxel (+/ÀBM) and zoledronate (+B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Mammographic density may therefore include effects of an altered matrix composition, in turn associated with carcinogenesis, whereas the tissue organization (MTR) may provide a score associated with local disorganization. The biological understanding of this being independent from matrix composition (density), may find support in other connective tissues and pathologies [29]. As tissue density and tissue distribution (MTR) were uncorrelated risk factors, this further supports that both accumulation and distribution are equally important for tissue function.…”
Section: Discussionmentioning
confidence: 79%
“…Mammographic density may therefore include effects of an altered matrix composition, in turn associated with carcinogenesis, whereas the tissue organization (MTR) may provide a score associated with local disorganization. The biological understanding of this being independent from matrix composition (density), may find support in other connective tissues and pathologies [29]. As tissue density and tissue distribution (MTR) were uncorrelated risk factors, this further supports that both accumulation and distribution are equally important for tissue function.…”
Section: Discussionmentioning
confidence: 79%
“…In this study, B-ALP (but not S-CTX and total ALP) responded to chemotherapy (24% decrease over 30 days). In a group of hormone refractory prostate cancer patients (n 5 40), S-CTX and total ALP did not decrease with Docetaxel therapy in patients without BM (13). However, it decreased with Docetaxel/Zoledronate treatment in those with BM (13).…”
Section: Resultsmentioning
confidence: 97%
“…It has been demonstrated that bisphosphonates, especially those of the last generation, induce a decrease in bone turnover marker expression, resulting in a significant reduction in skeletal complications and cancer-related deaths [4,5]. On the basis of this clinical evidence and of results from preclinical studies on the antitumor activity of different molecules, including zoledronic acid, bisphosphonates have been introduced into clinical practice as adjuvant treatment for the prevention of BM [6,7].…”
Section: Introductionmentioning
confidence: 99%